UNSUR CERITA PANJI DALAM PANJI KUDA NARAWANGSA - Dwi Yuliyanti (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This research aims to know the intrinsic and extrinsic elements of the panji story contained in the script Panji Kuda Narawangsa which is translated by Moelyono Sastronaryatmo and R. Aj. Indri Nitrani and its implications for literature learning in high school. The method used in this research is descriptive qualitative with content analysis technique. The focus of this research is the element of the banner story in the script Panji Kuda Narawangsa. The conclusions of this study are: (1) the most dominant theme in this story is the theme of romance, the other themes are the theme of incarnation and war, (2) there are main figures, supporting figures, and supporting figures, (3) setting of place and time dominated the story, (4) extrinsic elements of the panji story are religious values, cultural values, social values, and moral values. Keywords: Panji Kuda Narawangsa, story elements, hermeneutics Abstrak Penelitian ini bertujuan untuk mengetahui unsur intrinsik dan ekstrinsik cerita Panji yang terdapat dalam naskah Panji Kuda Narawangsa yang dialihbahasakan oleh Moelyono Sastronaryatmo dan R. Aj. Indri Nitrani dan implikasinya terhadap pembelajaran sastra di SMA. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan teknik analisis isi. Kesimpulan penelitian ini yaitu: (1) tema yang paling dominan dalam cerita Panji ini adalah tema percintaan, tema-tema yang lain adalah tema penjelmaan dan peperangan, (2) terdapat tokoh utama, tokoh pembantu, dan tokoh pendukung, (3) latar tempat dan latar waktu mendominasi cerita ini, (4) unsur ekstrinsik cerita panji berupa nilai agama, nilai budaya, nilai sosial, dan nilai moral. Kata kunci: Panji Kuda Narawangsa, unsur cerita, hermeneutika